Serum biochemistry profile of Clarias gariepinus (Burchell 1822) fingerlings fed varying levels of dietary maca (Lepidium meyenii, Walp.) root powder - Tahir, L. H.; Ali, M. E.; Kela, E.; Maisheru, J. A. (ADAN JOURNAL OF AGRICULTURE, 2026)
The serum biochemistry profile of Clarias gariepinus fingerlings fed varying levels of dietary maca (Lepidium meyenii, Walp.) root powder was investigated. Dietary maca root powder was included at: 0.0g/100g (TM1 i.e. control)), 0.25g/100g (TM2), 0.5g/100g (TM3,) 0.75g/100g (TM4) and 1.0g/100g (TM5) in triplicate, fed to C. gariepinus fingerlings (n = 300, 10.0±0.00g) in fifteen (15) plastic tanks (n = 20) at a fixed feeding rate of 3% body weight twice daily for twelve (12) weeks. Blood samples were collected for serum biochemical analysis. Data collected were analysed using one-way analysis of variance (ANOVA) at P = 0.05. Serum Total protein (4.15±0.7 – 4.85±0.1 g/dL), albumin (2.55±0.7 – 2.75±0.5 g/dL), globulin (1.60±0.03 – 2.10±0.07 g/dL), albumin/globulin (A: G) ratio (1.30±0.9 – 1.60±0.7), aspartate aminotransferase i.e. AST (32.60±2.7 – 33.65±1.4 U/L), alanine aminotransferase i.e. ALT (53.67±2.5 –54.80±2.8 U/L), glucose (313.10±1.8 – 320.30±1.6 mmol/L), potassium (2.58±0.4 – 3.00±0.3 mmol/L), sodium (136.10±1.8 – 142.20±1.2 mmol/L) and chlorine (106.20±1.2 – 110.50±1.7 mmol/L) respectively were obtained. The serum aspartate transaminase (AST), alanine aminotransferase (ALT) and glucose values recorded significant increases (P<0.05) with inclusion of maca root powder while potassium values decreased (P<0.05). Total serum protein, albumin, globulin, albumin/globulin (A: G) ratio, sodium and chlorine values were not significantly influenced (P>0.05) with the inclusion of maca root powder. Therefore, further study may be required to assess the suitability of dietary maca root powder at higher levels into formulated feed, its correlation with the various biological impacts, and the possible implication for human consumers.